Enhancing intercultural communication competence through situated learning: A mixed-methods study of international students in Taiwan - Lin, Pei-chih (Journal of International Students, 2026)
This study investigated the development of intercultural communication competence (ICC) among international students in Taiwan, examining the role of situated learning in fostering adaptation within authentic, nonclassroom contexts. A convergent parallel mixed-methods design was employed across two student cohorts. Quantitative data were collected through pre- and post-surveys using the Integrated Model of Intercultural Communication Competence (IMICC) and the Intercultural Adjustment Potential Scale (ICAPS). Qualitative data were gathered from students’ reflective journals, posters, and semistructured interviews. In a two-phase study structure, the first phase implemented a sequential situated learning experience, while the second phase compared the effects of direct (market visits) and indirect (documentary viewing) situated learning approaches. Quantitative findings revealed a modest overall increase in students’ self-assessed ICCs but a notable decrease in the cognitive competence subscale. Thematic analysis of the qualitative data explained this paradox, identifying cognitive disequilibrium as the central mechanism of development.